The Zero-Mach Limit of a Class of Combustion Flow (Journal of Partial Differential Equations, 2020)
The aim of this paper is to prove that compressible combustion flow in two and three space dimensions converges to the incompressible flow in the limit as the Mach number tends to zero.
Keywords: Zero-Mach limit; combustion equation; compressible; incompressible